Virtual Prediction of Phytosterol Compounds from Pegagan (Centella asiatica L.) As Inhibitor for Interleukin-6 (IL-6) to Prevent Rheumatoid Arthritis Disease - Azis Mawardi; Rossa Martha Wulandari; Moch Mustakim; Nurul Jadid Mubarakati (JSMARTech, 2023)
Rheumatoid arthritis (RA) is an autoimmune disease in which the joint area is inflamed which results in swelling, pain and often causes damage to the inside of the joint. Rheumatoid Arthritis is characterized by decreased Interleukin-6 (IL-6), so that Interleukin-6 (IL-6) inhibitors are needed. This strategy is convincing for controlling RA. Pegagan have to play role in overcoming the problem of joint inflammation. Phytosterols are compounds that are commonly found in pegagan and include antioxidants that are beneficial for health. This study aims to determine the mechanism pathway of pegagan's active compounds in the treatment of RA. This study used an in silico approach by analyzing target proteins and active compounds of pegagan through Lipinski rule of five and molecular docking analysis. This study used 3 phytosterol compounds including campesterol. β-sitosterol. and stigmasterol. The control used in this study was the tartaric acid compound whose receptor molecule was interleukin-6 (IL-6) with PDB ID: 1-ALU. The results of the Lipinski rule analysis found that all the test compounds used met the criteria and could be applied as drugs. Based on the results of molecular docking, stigmasterol has a good binding affinity value and is able to exceed the control compound with the highest binding affinity with score of -6.4 kcal/mol. Visualization results show that there is an interaction formed between the active compound and the target protein so that phytosterl compounds have a role that can be an alternative medicine in the prevention and treatment of RA.